Provide a model for reducing the administrative misconduct of agricultural production cooperatives with emphasis on organizational commitment - Dr. Morteza Moradi; Rabeah Zandipak (تعاون و کشاورزی, 2021)
The development of behaviors such as organizational justice, by increasing organizational obligations can be very effective in reducing administrative misconduct. The purpose of this study is to provide an effective model for reducing administrative misconduct among employees of agricultural production cooperatives with the mediating role of organizational commitment. The present study is applied in terms of purpose, descriptive-survey in terms of nature and method. To test the hypotheses, a 40-item questionnaire according to the Likert 7-choice spectrum was used. The statistical population of the study is the personnel of agricultural production cooperatives in Hamedan and Shiraz provinces with a total of 250 people. The statistical sample size of 148 people has been selected based on Krejcie and Morgan table by relative stratified method. The reliability of the analysis tool was confirmed using Cronbach's alpha coefficient and the validity of the tool was confirmed using construct validity through Lisrel software using confirmatory factor analysis. The path analysis model was used to analyze the findings and the Sobel test was used to analyze the mediating variable. The results showed that organizational justice and its components can have a negative and significant impact on administrative misconduct, directly and indirectly through organizational commitment.